Supply ranges of stone blocks used in masonry bridges and their construction period along the East Royal Road in the Khmer Empire, Cambodia - Etsuo Uchida; Yuichiro Sakurai; Rathborith Cheng; Ichita Shimoda; Yu Saito (Heritage Science, 2020)
Abstract During the Angkor period, there were five Royal Roads linking the capital city of Angkor with provincial principal cities. Seven Temples d’étape, six Fire Shrines, and 25 masonry bridges were constructed along the East Royal Road to Preah Khan of Kompong Svay. We conducted measurements of magnetic susceptibility and chemical composition of laterite blocks and magnetic susceptibility of sandstone blocks used for the construction of the bridges to determine the supply ranges of the stone blocks and the construction ages based on the results obtained in this study and previous studies of Temples d’étape and Fire Shrines. The results suggest that most of the sandstone blocks for the bridge balustrades were supplied from quarries in the southeastern foothills of Kulen Mountain, but that the bridges close to Preah Khan of Kompong Svay have sandstone balustrades supplied from nearby quarries. In contrast, cluster and principal component analyses and t-tests using data for chemical composition and magnetic susceptibility of laterite blocks revealed that there were five sources of supply. These results elucidated that the supply ranges of laterite blocks were narrower than those of the sandstone blocks. Judging from magnetic susceptibilities, supply ranges, shapes, orientations of bedding planes, and stacking methods of the stone blocks, it was concluded that the construction age of the bridges is highly likely to have been in the early Angkor Wat period.